32.8k views
5 votes
F(x) = x^3+3
g(x) = 2x +4
Find (f.g)(1)

User Kkyr
by
5.2k points

1 Answer

7 votes

Answer:


f(x).g(x) = ({x}^(3) + 3) * (2x + 4) \\ = ({x}^(3) * 2x) + ({x}^(3) * 4)+ (3 * 2x) + (3 * 4) \\ = 2 {x}^(4) + 4 {x}^(3) + 6x + 12 \\ (f.g)(1) = 2 ({1}^(4)) + 4 ({1}^(3))+ 6(1)+ 12 \\ = 2(1) + 4(1) + 6(1) + 12 \\ = 2 + 4 + 6 + 12 = 24 \\ (f.g)(1) = 24

Explanation:

I think this is the right answer, let me know.

User Iurii Drozdov
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.